Pengalaman Masalah Psikososial Korban Pemerkosaan: Literatur Review - Lutfi Nurdiansyah; Moch. Khoiru Fatta; Devi Wulandari; Suci Maulidiyah; Ana Aprilia (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
In modern times like today, many cases of sexual harassment such as rape are found where the majority of victims occur in women. This is because women tend to have a weak character, so that perpetrators are more flexible in controlling women in their disgraceful actions. Women who are victims of rape will have a very deep psychological trauma. The purpose of this literature study is to determine the psychosocial problems of rape victims. The method used is a literature study of journal articles with criteria related to the topic of this research. The selection of journals is carried out on a database of scientific articles such as Google Scholar, with full text criteria, and in 2013-2022. The results showed that rape victims had deep psychological trauma, thought they had low self-esteem. Assistance from families and social workers in the recovery process of rape victims is needed so that victims can restore their self-image.